Analysis of Total Coliform and Total Escherichia coli Levels in the Fox River Watershed - Romesberg, Janée; Henderson, Jeffrey O. (Journal of Student Research, 2018)
The Fox River is an important water source for the Elgin, IL community. Fecal contaminants must be removed by water treatment facilities to prevent the spread of infectious diseases and to provide potable water. Water samples from the Fox River watershed on or near Judson University campus were tested using the most probable number (MPN) method to determine coliform counts. Our data from this small independent project demonstrates that tap water is free of fecal contaminants and that the Fox River, its tributary Tyler Creek, and the Volkman Retention Pond often have levels of coliforms exceeding standards for recreational use.